The attitudes of Jordanian English language and literature undergraduate students toward open-book exams - Abu-Snoubar, Tamador Khalaf; Aldowkat, Issam; Al-Shboul, Yasser; Atiyat, Mona Ahmad; Al-Hyari, Hadeel (Frontiers in Education, 2022)
Abstract The paper aims to investigate the attitudes of English Language and Literature students toward implementing the open-book exam in literature courses. The research applied a mixed method approach. The researchers interviewed five undergraduate students enrolled in American Literature course at Al-Balqa Applied University, Jordan for the qualitative part, whereas the research includes results of 62 questionnaires for the quantitative part. Moreover, a survey questionnaire was developed by the researchers to collect the data concerning the participants’ attitudes towards OBEs. The study found positive attitude towards OBEs. Moreover, the study participants demonstrated that OBEs reduces stress levels which occur during exams in general. Statistical representation of the findings showed that the sample students have a positive attitude in relation to this unconventional assessment protocol. OBEs should be allowed more space in the academic institutions since today’s world does not depend on the amount of information a job applicant deposits in his memory. What matters is if the person possesses enough high-order thinking abilities and skills like problem-solving.